Identification of Connectivity and Citizenship Ability of Biology Students at SMAN 12 Padang - Nurulita Spahira Anjani Putri W; Relsas Yogica; Ardi Ardi; Rahmadhani Fitri (PALAPA, 2023)
This study aims to find out how connectivity and citizenship skills are part of the 21st Century 6C skills in biology students. This is important to know because currently students are in the era of revolution 4.0 and will continue to compete with the times, where preparations for the future job market are more focused on soft skills than hard skills. This type of research is a quantitative descriptive research. The sample in this study were students in class XI-IPA with a total sampling technique of 180 people. The instrument used is a questionnaire with a Likert scale. Data collection technique with a closed questionnaire. The data analysis technique is by converting students' raw scores. Based on the research, it was found that the connectivity ability of the students was 81.62% which was included in the "very high" category, while in the citizenship ability the results obtained were 79.70% which were included in the "very high" category . Based on the results of the study it was found that students were able to compete with the times in the future.